2022
DOI: 10.3390/w14233920
|View full text |Cite
|
Sign up to set email alerts
|

Mass Variations in Terrestrial Water Storage over the Nile River Basin and Mega Aquifer System as Deduced from GRACE-FO Level-2 Products and Precipitation Patterns from GPCP Data

Abstract: Changes in the terrestrial total water storage (TWS) have been estimated at both global and river basin scales from the Gravity Recovery and Climate Experiment (GRACE) mission and are still being detected from its GRACE Follow-On (GRACE-FO) mission. In this contribution, the sixth release of GRACE-FO (RL06) level-2 products applying DDK5 (decorrelation filter) were used to detect water mass variations for the Nile River Basin (NRB) in Africa and the Mega Aquifer System (MAS) in Asia. The following approach was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…The majority of previous studies on the principal wadis in the Western Area revealed that rock types and agricultural activities are the primary factors of groundwater salinity [1,2]. Furthermore, location-dependent, local geological, morphological, tectonic, and climatological factors influence the availability of groundwater supplies [3][4][5][6][7][8][9][10]. In arid areas, the alluvium fractures and also fills with the majority of the water.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of previous studies on the principal wadis in the Western Area revealed that rock types and agricultural activities are the primary factors of groundwater salinity [1,2]. Furthermore, location-dependent, local geological, morphological, tectonic, and climatological factors influence the availability of groundwater supplies [3][4][5][6][7][8][9][10]. In arid areas, the alluvium fractures and also fills with the majority of the water.…”
Section: Introductionmentioning
confidence: 99%
“…These two missions provide a unique tool for determining the temporal variations of gravity; consequently, the mass redistribution processes that have generated the gravity changes [4]. GRACE and GRACE-FO have become essential sources of data when monitoring the variation in water fluxes over large basins (e.g., the Mediterranean Sea [5], the Arabian Peninsula [6][7][8], Niger [9], Michigan [10], the Amazonas [11][12][13], the La Plata basins [14,15], the Nubian and Nile basins [16][17][18][19][20][21]), and for the analysis of climate changes via ice mass balance [22][23][24], sea level rise [25,26], ground water storage [27][28][29][30][31], and extreme precipitation [32]. In the present study, a GRACE-and GRACE-FO-based gravity anomaly time series is determined and utilized to analyze the desiccation process of the Aral Sea.…”
Section: Introductionmentioning
confidence: 99%